(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
This article offers a conceptual and methodological apparatus for assessing periods of contemporary history. Using this apparatus and empirical data from the development of Eastern European and northern Eurasian countries over the last forty years, the article analyzes the establishment, evolution, and decline of the post-Soviet period. These developmental processes are conceptualized in terms of five categories: democratization, autocratization, marketization, nationalization, and Europeanization. The article concludes that the post-Soviet period and its structural processes have ended, and Europe and Eurasia must undergo the process of remapping their geography and adjusting their regional temporalities.